2009
DOI: 10.5694/j.1326-5377.2009.tb03355.x
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of disease awareness advertisements in popular Australian women's magazines

Abstract: Objective: To examine the nature of disease awareness advertising (DAA). Design: Therapeutic advertisements in six popular Australian women's magazines were monitored between April 2006 and March 2007. A subset of advertisements was included in the study based on criteria derived from a definition of DAA. Unique advertisements were analysed by four independent coders. Main outcome measures: Types of advertisements and their sponsors, the types of disease information present, and the persuasive techniques utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Our results seem to indicate that pharmaceutical companies often opt to reach a wider audience by publishing their unbranded product advertisements in free media outlets, most notably in dedicated health-supplements. The frequency of occurrence of disease awareness campaigns observed in our study is consistent with the results of an Australian study, where a total of sixty campaigns were identified in popular women's magazines over eleven months [22]. From these, fifteen contained a corporate brand or logo – a result also similar to ours.…”
Section: Discussionsupporting
confidence: 91%
“…Our results seem to indicate that pharmaceutical companies often opt to reach a wider audience by publishing their unbranded product advertisements in free media outlets, most notably in dedicated health-supplements. The frequency of occurrence of disease awareness campaigns observed in our study is consistent with the results of an Australian study, where a total of sixty campaigns were identified in popular women's magazines over eleven months [22]. From these, fifteen contained a corporate brand or logo – a result also similar to ours.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the limited literature on consumers' responses to DAA, there is some evidence that this advertising increases awareness of the advertised health conditions and prescriptions of the sponsor's product (Basara, 1996; t'Jong et al ., 2004). A recent content analysis examined the prevalence of DAA in top circulating Australian women's magazines and concluded it constituted approximately 12% of all therapeutic advertisements (Hall et al ., 2009); this finding suggests its potential exposure is at least moderate.…”
Section: Introductionmentioning
confidence: 84%
“…The waiting room pamphlet was shown to improve dementia risk reduction knowledge further. This informative pamphlet may counteract the deficit shown in standard waiting room material with a survey of women's magazines in Australia between 2006 and 2007 revealing no mention of dementia (Hall et al 2009). The use of relevant health information in GP waiting rooms, especially a free pamphlet that can be downloaded from the Alzheimer's Australia website, can assist patient health literacy.…”
Section: Discussionmentioning
confidence: 99%